A cement-based material admixture based on machine-made sand tailings and a preparation method thereof
Through chemical activation and surfactant treatment mechanism, sand tail puree, and mix with high -active limestone, nano -silicon dioxide and chemical modifiers, prepare the mixing material of cement base materials, solve the mechanism of the utilization utilization rate of tail mud resourceization, Low problems have achieved a large amount of resource utilization of large quantities and low energy consumption.
Patent Information
- Application Number
- CN202411095351.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-08-12
- Publication Date
- 2025-01-28
- Estimated Expiration
- 2044-08-12
Abstract
Description
Technical Field
[0001] The invention belongs to the field of environmentally friendly building materials and relates to cement-based materials, and in particular to a cement-based material admixture based on machine-made sand tailings and a preparation method thereof. Background Art
[0002] Artificial sand is made from rocks through mechanical crushing and screening. Its particle size distribution and physical properties can be controlled and optimized through the production process. It has the characteristics of good particle shape and high stability. It has replaced natural sand and is widely used in building materials such as concrete and mortar. The production of artificial sand is mainly divided into two types: dry method and wet method. Among them, the wet method can remove the soil and impurities on the surface of artificial sand particles during the sand washing process, and the produced artificial sand is cleaner. In addition, the wet method can better control dust pollution, so the wet method is more commonly used. However, during the sand washing process, the fine particles and soil in the artificial sand are carried away by the water flow to form tailings. The tailings are complex in composition, mainly composed of stone powder, soil, mineral particles and water, and its particle size is usually less than 75 microns. These fine particles are difficult to process by conventional mechanical methods due to their small particle size and large specific surface area, resulting in a large amount of tailings that are difficult to be effectively recycled.
[0003] At present, the methods for processing machine-made sand tailings are to use a certain amount of mud powder contained therein to burn materials such as ceramsite, bricks, and ceramics, thereby realizing the resource utilization of machine-made sand tailings. However, the above methods all require high-temperature sintering or curing, with high energy consumption and carbon emissions, and it is difficult to dispose of machine-made sand tailings in large quantities, and it is impossible to achieve its efficient utilization. In addition, CN110922074A introduces a method for preparing cement clinker using machine-made sand plant sludge instead of clay as a raw material for raw materials. This method can use a large amount of machine-made sand tailings, but it still needs to be heated to 1350-1450°C, and the energy consumption is relatively high. CN116177974A proposes a method for preparing a self-compacting backfill material of machine-made sand tailings based on phosphogypsum, which mainly uses a gypsum-based binder as a curing agent, and the backfill material has a low compressive strength and a limited scope of application.
[0004] Therefore, stimulating the reaction activity of machine-made sand tailings and improving the performance of the reaction products of machine-made sand tailings will lay the foundation for its use in the preparation of cement mortar and concrete, and can realize the large-scale resource utilization of machine-made sand tailings, which has significant economic benefits and environmental protection significance. Summary of the invention
[0005] In view of the problems of low resource utilization rate, low disposal efficiency and high disposal cost of machine-made sand tailings in the prior art, the present invention provides a cement-based material admixture based on machine-made sand tailings and a preparation method thereof. The present invention can realize large-scale low-energy consumption disposal of machine-made sand tailings, facilitates the application of machine-made sand tailings in cement mortar and concrete, and realizes resource utilization.
[0006] The technical solution adopted by the present invention to solve the technical problem is as follows: the cement-based material admixture based on machine-made sand tailings and the preparation method thereof are specifically divided into the following steps:
[0007] (1) Mix the machine-made sand tailings and chemical activator in a mass ratio of 100:5-10 and stir using a high-speed mixer;
[0008] (2) placing the mixture in a dry environment, adding a surfactant and stirring evenly, and then applying ultrasound for 6-24 hours to promote and catalyze the activation reaction to obtain activated machine-made sand tailings;
[0009] (3) Use a constant temperature drying oven to dry the activated machine-made sand tailings, add desiccant to accelerate drying, and control the drying temperature at 60°C-80°C until it is completely dry;
[0010] (4) The dried material is preliminarily crushed with a pulverizer to a particle size of less than 1 mm, a grinding aid is added to the preliminarily crushed material, and then the material is placed in a ball mill or a vibration mill for further crushing to a particle size of less than 100 meshes to obtain activated machine-made sand tailings powder;
[0011] (5) Mix activated machine-made sand tailings powder, high-activity lime powder, nano-silicon dioxide, and chemical modifier in a mass ratio of 100:1-5:2-4:1-5, and prepare a cement-based material admixture after stirring.
[0012] Preferably, in step (1), the chemical activator is one of materials selected from the group consisting of sodium hydroxide, potassium hydroxide, calcium silicate, calcium aluminate, calcium phosphate, and calcium aluminosilicate.
[0013] Preferably, in step (1), the stirring speed is controlled at 300-500 rpm, and the stirring time is controlled at 5-10 minutes.
[0014] Preferably, in step (2), the surfactant is one of materials such as sodium dodecyl sulfate, nonylphenol polyoxyethylene ether, polyethylene glycol oleate, alkylphenol polyoxyethylene ether, etc., and the amount used is 2%-4% of the mass of the machine-made sand tailings.
[0015] Preferably, in step (2), the frequency of the ultrasonic wave is controlled within a range of 20 kHz to 100 kHz.
[0016] Preferably, in step (3), the desiccant is anhydrous calcium sulfate, and the amount used is 0.5%-1% of the mass of the machine-made sand tailings.
[0017] Preferably, in step (4), the grinding aid is one of sodium stearate and polyolamine, and the amount used is 0.01%-0.1% of the mass of the machine-made sand tailings.
[0018] Preferably, in step (5), the calcium oxide content of the high-activity lime powder is greater than 90 wt % and the particle size is less than 100 μm.
[0019] Preferably, in step (5), the SiO2 content of the nano-silicon dioxide is greater than 99 wt% and the particle size is less than 100 nm.
[0020] Preferably, in step (5), the chemical modifier is one of triethanolamine, triisomethanolamine, dimethylethanolamine and the like.
[0021] The beneficial effects of the present invention are:
[0022] (1) The present invention adopts a chemical activation method to improve the chemical reaction activity of machine-made sand tailings, making it possible to use the machine-made sand tailings in the preparation and production of building materials such as cement mortar and concrete, and helping to achieve large-scale resource utilization of machine-made sand tailings.
[0023] (2) The present invention uses surfactants and ultrasound to produce activated machine-made sand tailings, which can reduce the surface tension of machine-made sand tailings particles, enhance the dispersibility of machine-made sand tailings particles during the drying stage, and increase the activation reaction rate, which is conducive to the full occurrence of the machine-made sand activation reaction. At the same time, it can also improve the chemical reaction activity of the machine-made sand tailings to a certain extent.
[0024] (3) The present invention mixes activated machine-made sand tailings powder with high-activity lime powder, nano-silicon dioxide, and a chemical modifier to prepare a cement-based material admixture. The high-activity lime powder, nano-silicon dioxide, and chemical modifier further improve the reaction activity of the prepared cement-based material admixture, thereby enhancing the mechanical properties and durability of the prepared cement-based material.
[0025] (4) The drying temperature of the present invention is 60-80°C, which significantly reduces the energy consumption and pollution emissions of the resource utilization of machine-made sand tailings. The material preparation method is simple and easy to operate, and has good economic benefits and environmental protection significance. DETAILED DESCRIPTION
[0026] The present invention will be further described below in conjunction with embodiments:
[0027] The present invention will be further described below in conjunction with specific examples. It should be understood that these examples are only used to illustrate the present invention and are not intended to limit the scope of the present invention. The experimental methods in the following examples without specifying specific conditions are usually carried out under conventional conditions or according to the conditions recommended by the manufacturer.
[0028] Unless otherwise defined, all professional and scientific terms used herein have the same meanings as those familiar to those skilled in the art. The reagents or raw materials used in the present invention can be purchased through conventional channels. Unless otherwise specified, the reagents or raw materials used in the present invention are used in a conventional manner in the art or in accordance with the product instructions. In addition, any method and material similar to or equivalent to the described content can be applied to the method of the present invention. The preferred implementation methods and materials in the text are for demonstration purposes only.
[0029] Example 1
[0030] A cement-based material admixture based on machine-made sand tailings and a preparation method thereof, comprising the following steps:
[0031] (1) Mix the machine-made sand tailings and sodium hydroxide in a mass ratio of 100:10 and stir them using a high-speed mixer at a stirring speed of 500 rpm for 10 minutes.
[0032] (2) The mixture was placed in a dry environment, sodium dodecyl sulfate (4% by mass of the machine-made sand tailings) was added, the mixture was stirred evenly, and the reaction was accelerated by ultrasound for 24 hours at an ultrasonic frequency of 100 kHz to obtain activated machine-made sand tailings.
[0033] (3) Use a constant temperature drying oven to dry the activated machine-made sand tailings, add 1% of the mass of the machine-made sand tailings anhydrous calcium sulfate, and control the drying temperature at 80°C until the material is completely dry.
[0034] (4) The dried material is preliminarily crushed with a pulverizer to a particle size of less than 1 mm. Sodium stearate at 0.1% of the mass of the machine-made sand tailings is added to the preliminarily crushed material, and then the material is placed in a ball mill or a vibration mill for further crushing to a particle size of less than 100 meshes to obtain activated machine-made sand tailings powder.
[0035] (5) The activated machine-made sand tailings powder, high-activity lime powder, nano-silicon dioxide and triethanolamine are mixed in a mass ratio of 100:5:4:5 and stirred to obtain a cement-based material admixture.
[0036] Example 2
[0037] (1) Mix the machine-made sand tailings and sodium hydroxide in a mass ratio of 100:5 and stir them using a high-speed mixer. The stirring speed is controlled at 300 rpm and the stirring time is 5 minutes.
[0038] (2) The mixture was placed in a dry environment, and sodium dodecyl sulfate (2% by mass of the machine-made sand tailings) was added and stirred evenly. The reaction was accelerated by ultrasound for 6 hours at an ultrasonic frequency of 20 kHz to obtain activated machine-made sand tailings.
[0039] (3) Use a constant temperature drying oven to dry the activated machine-made sand tailings, add 0.5% of the mass of the machine-made sand tailings anhydrous calcium sulfate, and control the drying temperature at 60°C until the material is completely dry.
[0040] (4) The dried material is preliminarily crushed with a pulverizer to a particle size of less than 1 mm. Sodium stearate at 0.01% of the mass of the machine-made sand tailings is added to the preliminarily crushed material, and then the material is placed in a ball mill or a vibration mill for further crushing to a particle size of less than 100 meshes to obtain activated machine-made sand tailings powder.
[0041] (5) Activated machine-made sand tailings powder, high-activity lime powder, nano-silicon dioxide and triethanolamine are mixed in a mass ratio of 100:1:2:1, and stirred to obtain a cement-based material admixture.
[0042] Example 3
[0043] (1) Mix the machine-made sand tailings and potassium hydroxide in a mass ratio of 100:6 and stir them using a high-speed mixer. The stirring speed is controlled at 400 rpm and the stirring time is 6 minutes.
[0044] (2) The mixture was placed in a dry environment, and 3% of the mass of machine-made sand tailings nonylphenol polyoxyethylene ether was added, stirred evenly, and subjected to ultrasonic accelerated reaction for 12 hours at an ultrasonic frequency of 30 kHz to obtain activated machine-made sand tailings.
[0045] (3) Use a constant temperature drying oven to dry the activated machine-made sand tailings, add 0.6% of the mass of the machine-made sand tailings anhydrous calcium sulfate, and control the drying temperature at 70°C until the material is completely dry.
[0046] (4) The dried material is preliminarily crushed with a pulverizer to a particle size of less than 1 mm. 0.02% of the mass of the machine-made sand tailings is added to the preliminarily crushed material, and then the material is further crushed in a ball mill or a vibration mill to a particle size of less than 100 meshes to obtain activated machine-made sand tailings powder.
[0047] (5) The activated machine-made sand tailings powder, high-activity lime powder, nano-silica and triisomethanolamine are mixed in a mass ratio of 100:2:3:2, and the mixture is stirred to obtain a cement-based material admixture.
[0048] Example 4
[0049] (1) Mix the machine-made sand tailings and calcium silicate in a mass ratio of 100:7 and stir them using a high-speed mixer. The stirring speed is controlled at 500 rpm and the stirring time is 7 minutes.
[0050] (2) The mixture was placed in a dry environment, and 4% of the mass of the machine-made sand tailings polyethylene glycol oleate was added, stirred evenly, and subjected to ultrasonic accelerated reaction for 18 hours at an ultrasonic frequency of 40 kHz to obtain activated machine-made sand tailings.
[0051] (3) Use a constant temperature drying oven to dry the activated machine-made sand tailings, add 0.7% of the mass of the machine-made sand tailings anhydrous calcium sulfate, and control the drying temperature at 80°C until the material is completely dry.
[0052] (4) The dried material is preliminarily crushed with a pulverizer to a particle size of less than 1 mm. Sodium stearate at a rate of 0.03% of the mass of the machine-made sand tailings is added to the preliminarily crushed material, and then the material is further crushed in a ball mill or a vibration mill to a particle size of less than 100 meshes to obtain activated machine-made sand tailings powder.
[0053] (5) The activated machine-made sand tailings powder, high-activity lime powder, nano-silicon dioxide and dimethylethanolamine were mixed in a mass ratio of 100:3:4:3, and the mixture was stirred to obtain a cement-based material admixture.
[0054] Example 5
[0055] (1) Mix the machine-made sand tailings and calcium aluminate in a mass ratio of 100:8 and stir them using a high-speed mixer at a stirring speed of 300 rpm for 8 minutes.
[0056] (2) The mixture was placed in a dry environment, 2% of the mass of the machine-made sand tailings was added with alkylphenol polyoxyethylene ether, stirred evenly, and subjected to ultrasonic accelerated reaction for 24 hours at an ultrasonic frequency of 50 kHz to obtain activated machine-made sand tailings.
[0057] (3) Use a constant temperature drying oven to dry the activated machine-made sand tailings, add 0.8% of the mass of the machine-made sand tailings anhydrous calcium sulfate, and control the drying temperature at 60°C until the material is completely dry.
[0058] (4) The dried material is preliminarily crushed with a pulverizer to a particle size of less than 1 mm. 0.04% of the mass of the machine-made sand tailings is added to the preliminarily crushed material, and then the material is further crushed in a ball mill or a vibration mill to a particle size of less than 100 meshes to obtain activated machine-made sand tailings powder.
[0059] (5) The activated machine-made sand tailings powder, high-activity lime powder, nano-silicon dioxide and triethanolamine are mixed in a mass ratio of 100:4:2:4, and the mixture is stirred to obtain a cement-based material admixture.
[0060] Example 6
[0061] (1) Mix the machine-made sand tailings and calcium phosphate in a mass ratio of 100:9 and stir them using a high-speed mixer at a stirring speed of 400 rpm for 9 minutes.
[0062] (2) The mixture was placed in a dry environment, and sodium dodecyl sulfate (3% by mass of the machine-made sand tailings) was added and stirred evenly. The reaction was accelerated by ultrasound for 6 hours at an ultrasonic frequency of 60 kHz to obtain activated machine-made sand tailings.
[0063] (3) Use a constant temperature drying oven to dry the activated machine-made sand tailings, add 0.9% of the mass of the machine-made sand tailings anhydrous calcium sulfate, and control the drying temperature at 70°C until the material is completely dry.
[0064] (4) The dried material is preliminarily crushed with a pulverizer to a particle size of less than 1 mm. Sodium stearate at a rate of 0.05% of the mass of the machine-made sand tailings is added to the preliminarily crushed material, and then the material is placed in a ball mill or a vibration mill for further crushing to a particle size of less than 100 meshes to obtain activated machine-made sand tailings powder.
[0065] (5) Activated machine-made sand tailings powder, high-activity lime powder, nano-silica, and triisomethanolamine are mixed in a mass ratio of 100:5:3:5, and stirred to obtain a cement-based material admixture.
[0066] Example 7
[0067] (1) Mix the machine-made sand tailings and calcium aluminosilicate in a mass ratio of 100:10 and stir them using a high-speed mixer at a stirring speed of 500 rpm for 10 minutes.
[0068] (2) The mixture was placed in a dry environment, and 4% of the mass of the machine-made sand tailings nonylphenol polyoxyethylene ether was added, stirred evenly, and subjected to ultrasonic accelerated reaction for 12 hours at an ultrasonic frequency of 70 kHz to obtain activated machine-made sand tailings.
[0069] (3) Use a constant temperature drying oven to dry the activated machine-made sand tailings, add 1% of the mass of the machine-made sand tailings anhydrous calcium sulfate, and control the drying temperature at 80°C until the material is completely dry.
[0070] (4) The dried material is preliminarily crushed with a pulverizer to a particle size of less than 1 mm. 0.06% of the mass of the machine-made sand tailings is added to the preliminarily crushed material, and then the material is further crushed in a ball mill or a vibration mill to a particle size of less than 100 meshes to obtain activated machine-made sand tailings powder.
[0071] (5) The activated machine-made sand tailings powder, high-activity lime powder, nano-silicon dioxide and dimethylethanolamine were mixed in a mass ratio of 100:1:4:1, and the mixture was stirred to obtain a cement-based material admixture.
[0072] Example 8
[0073] (1) Mix the machine-made sand tailings and sodium hydroxide in a mass ratio of 100:10 and stir them using a high-speed mixer at a stirring speed of 500 rpm for 10 minutes.
[0074] (2) The mixture was placed in a dry environment, and sodium dodecyl sulfate (2% by mass of the machine-made sand tailings) was added and stirred evenly. The reaction was accelerated by ultrasound for 6 hours at an ultrasonic frequency of 80 kHz to obtain activated machine-made sand tailings.
[0075] (3) Use a constant temperature drying oven to dry the activated machine-made sand tailings, add 0.5% of the mass of the machine-made sand tailings anhydrous calcium sulfate, and control the drying temperature at 60°C until the material is completely dry.
[0076] (4) The dried material is preliminarily crushed with a pulverizer to a particle size of less than 1 mm. Sodium stearate at a rate of 0.07% of the mass of the machine-made sand tailings is added to the preliminarily crushed material, and then the material is placed in a ball mill or a vibration mill for further crushing to a particle size of less than 100 meshes to obtain activated machine-made sand tailings powder.
[0077] (5) Activated machine-made sand tailings powder, high-activity lime powder, nano-silicon dioxide and triethanolamine are mixed in a mass ratio of 100:1:2:1, and stirred to obtain a cement-based material admixture.
[0078] Example 9
[0079] (1) Mix the machine-made sand tailings and sodium hydroxide in a mass ratio of 100:5 and stir them using a high-speed mixer. The stirring speed is controlled at 300 rpm and the stirring time is 5 minutes.
[0080] (2) The mixture was placed in a dry environment, and sodium dodecyl sulfate (4% by mass of the machine-made sand tailings) was added and stirred evenly. The reaction was accelerated by ultrasound for 24 hours at a frequency of 90 kHz to obtain activated machine-made sand tailings.
[0081] (3) Use a constant temperature drying oven to dry the activated machine-made sand tailings, add 0.5% of the mass of the machine-made sand tailings anhydrous calcium sulfate, and control the drying temperature at 60°C until the material is completely dry.
[0082] (4) The dried material is preliminarily crushed with a pulverizer to a particle size of less than 1 mm. Sodium stearate at a rate of 0.08% of the mass of the machine-made sand tailings is added to the preliminarily crushed material, and then the material is placed in a ball mill or a vibration mill for further crushing to a particle size of less than 100 meshes to obtain activated machine-made sand tailings powder.
[0083] (5) Activated machine-made sand tailings powder, high-activity lime powder, nano-silicon dioxide and triethanolamine are mixed in a mass ratio of 100:1:2:1, and stirred to obtain a cement-based material admixture.
[0084] Example 10
[0085] (1) Mix the machine-made sand tailings and sodium hydroxide in a mass ratio of 100:5 and stir them using a high-speed mixer. The stirring speed is controlled at 300 rpm and the stirring time is 5 minutes.
[0086] (2) The mixture was placed in a dry environment, and sodium dodecyl sulfate (2% by weight of the machine-made sand tailings) was added and stirred evenly. The reaction was accelerated by ultrasound for 6 hours at an ultrasonic frequency of 100 kHz to obtain activated machine-made sand tailings.
[0087] (3) Use a constant temperature drying oven to dry the activated machine-made sand tailings, add 1% of the mass of the machine-made sand tailings anhydrous calcium sulfate, and control the drying temperature at 80°C until the material is completely dry.
[0088] (4) The dried material is preliminarily crushed with a pulverizer to a particle size of less than 1 mm. Sodium stearate at a rate of 0.09% of the mass of the machine-made sand tailings is added to the preliminarily crushed material, and then the material is placed in a ball mill or a vibration mill for further crushing to a particle size of less than 100 meshes to obtain activated machine-made sand tailings powder.
[0089] (5) Activated machine-made sand tailings powder, high-activity lime powder, nano-silicon dioxide and triethanolamine are mixed in a mass ratio of 100:1:2:1, and stirred to obtain a cement-based material admixture.
[0090] Embodiment 11
[0091] (1) Mix the machine-made sand tailings and sodium hydroxide in a mass ratio of 100:5 and stir them using a high-speed mixer. The stirring speed is controlled at 300 rpm and the stirring time is 5 minutes.
[0092] (2) The mixture was placed in a dry environment, and sodium dodecyl sulfate (2% by mass of the machine-made sand tailings) was added and stirred evenly. The reaction was accelerated by ultrasound for 6 hours at an ultrasonic frequency of 20 kHz to obtain activated machine-made sand tailings.
[0093] (3) Use a constant temperature drying oven to dry the activated machine-made sand tailings, add 0.5% of the mass of the machine-made sand tailings anhydrous calcium sulfate, and control the drying temperature at 60°C until the material is completely dry.
[0094] (4) The dried material is preliminarily crushed with a pulverizer to a particle size of less than 1 mm. Sodium stearate at 0.1% of the mass of the machine-made sand tailings is added to the preliminarily crushed material, and then the material is placed in a ball mill or a vibration mill for further crushing to a particle size of less than 100 meshes to obtain activated machine-made sand tailings powder.
[0095] (5) The activated machine-made sand tailings powder, high-activity lime powder, nano-silicon dioxide and triethanolamine are mixed in a mass ratio of 100:5:4:5 and stirred to obtain a cement-based material admixture.
[0096] Comparative Example 1
[0097] Compared with Example 1, Comparative Example 1 is different in that: in step (1) of Example 1, no sodium hydroxide is added.
[0098] Comparative Example 2
[0099] Compared with Example 1, Comparative Example 2 is different in that: in step (2) of Example 1, sodium dodecyl sulfate is not added.
[0100] Comparative Example 3
[0101] Compared with Example 1, Comparative Example 3 is different in that: in step (2) of Example 1, ultrasound is not used to accelerate the reaction.
[0102] Comparative Example 4
[0103] Compared with Example 1, Comparative Example 4 is different in that: in step (3) of Example 1, anhydrous calcium sulfate is not added.
[0104] Comparative Example 5
[0105] Compared with Example 1, the difference of Comparative Example 5 is that in step (4) of Example 1, sodium stearate is not added.
[0106] Comparative Example 6
[0107] Compared with Example 1, Comparative Example 6 is different in that: in step (5) of Example 1, high-activity lime powder is not added.
[0108] Comparative Example 7
[0109] Compared with Example 1, Comparative Example 7 is different in that: in step (5) of Example 1, nano-silicon dioxide is not added.
[0110] Comparative Example 8
[0111] Compared with Example 1, Comparative Example 8 is different in that: in step (5) of Example 1, no triethanolamine is added.
[0112] The activity index of activated machine sand tailings as mineral admixture was tested according to the Technical Specification for Application of Mineral Admixtures (GB / T 51003). The test method is consistent with the activity index test of zeolite powder. The test results are shown in Table 1.
[0113] Table 1 Specific implementation test results
[0114] Test items Example 1 Example 2 Example 3 Example 4 Example 5 Example 6 Example 7 Example 8 Example 9 Example 10 Embodiment 11 Activity Index 0.84 0.72 0.76 0.78 0.78 0.80 0.79 0.77 0.79 0.75 0.80 Test items Comparative Example 1 Comparative Example 2 Comparative Example 3 Comparative Example 4 Comparative Example 5 Comparative Example 6 Comparative Example 7 Comparative Example 8 Activity Index 0.64 0.69 0.66 0.71 0.73 0.64 0.65 0.62
[0115] It can be seen from the above data that the activity indexes of Examples 1-11 are all above 0.70, which can realize the application of activated machine tailings in cement mortar and concrete. Compared with Example 1, the machine tailings in Example 1 were not activated, and its activity index was much lower than that of Example 1. No surfactant was added to Example 2, and no ultrasonic catalytic activation reaction was used in Example 3, and their activity indexes were also much lower than that of Example 1. No desiccant and grinding aid were added to Examples 4 and 5, respectively, which would affect the performance of the final admixtures, and the activity index was lower than that of Example 1. The missing raw materials in Examples 6-8 are the key to further improving the activity index of the final admixtures, so their activity indexes are much lower than that of Example 1.
[0116] The use of chemical activators can improve the activity of machine-made sand tailings, surfactants can fully disperse the machine-made sand tailings, and with ultrasonic catalysis, the reaction activity and rate can be further improved. After drying and crushing, activated modified machine-made sand tailings are formed, and then combined with high-activity lime powder, nano-silicon dioxide, and chemical modifiers, the activity index of the prepared admixture can be higher than 0.70, which can be used in the preparation of mud mortar and concrete, realizing the resource utilization of machine-made sand tailings.
[0117] Certain words are used in the specification and claims of the present invention to refer to specific products. It should be understood by those skilled in the art that manufacturers may refer to the same component by different names. It is not intended to distinguish between components that have the same function but different names. In the following specification and patent scope, the words "comprise", "have" and "include" are open-ended words and should be interpreted as "including but not limited to...".
[0118] The above is a preferred embodiment of the present invention. It should be pointed out that a person skilled in the art can make several improvements and modifications without departing from the principle of the present invention. These improvements and modifications are also considered to be within the scope of protection of the present invention.
Claims
1. A method for preparing a cement-based material admixture based on machine-made sand tailings, characterized in that: The following steps are involved: (1) Mix the machine-made sand tailings and chemical activator in a mass ratio of 100:5-10 and stir using a high-speed mixer; (2) placing the mixture in a dry environment, adding a surfactant and stirring evenly, and then applying ultrasound for 6-24 hours to promote and catalyze the activation reaction to obtain activated machine-made sand tailings; (3) Use a constant temperature drying oven to dry the activated sand tailings, add desiccant, and control the drying temperature at 60°C~80°C until it is completely dry; (4) The dried material is preliminarily crushed by a pulverizer to a particle size of less than 1 mm, a grinding aid is added to the preliminarily crushed material, and then the material is further crushed in a ball mill or a vibration mill to a particle size of less than 100 meshes to obtain activated machine-made sand tailings powder; (5) Mixing activated machine-made sand tailings powder, high-activity lime powder, nano-silicon dioxide, and a chemical modifier in a mass ratio of 100:1-5:2-4:1-5, and stirring to obtain the cement-based material admixture; The chemical activator is one of sodium hydroxide, potassium hydroxide, calcium silicate, calcium aluminate, calcium phosphate, and calcium aluminosilicate; The chemical modifier is one of triethanolamine, triisomethanolamine and dimethylethanolamine.
2. The method for preparing a cement-based material admixture based on machine-made sand tailings according to claim 1, characterized in that: The stirring speed of the high-speed stirrer is controlled at 300-500 rpm, and the stirring time is 5-10 minutes.
3. The method for preparing a cement-based material admixture based on machine-made sand tailings according to claim 1, characterized in that: The surfactant is one of sodium dodecyl sulfate, nonylphenol polyoxyethylene ether, polyethylene glycol oleate, and alkylphenol polyoxyethylene ether, and the dosage is 2% to 4% of the mass of the machine-made sand tailings.
4. The method for preparing a cement-based material admixture based on machine-made sand tailings according to claim 1, characterized in that: The frequency of the ultrasonic wave is controlled to be between 20 kHz and 100 kHz.
5. The method for preparing a cement-based material admixture based on machine-made sand tailings according to claim 1, characterized in that: The desiccant is anhydrous calcium sulfate, and the dosage is 0.5% to 1% of the mass of the machine-made sand tailings.
6. The method for preparing a cement-based material admixture based on machine-made sand tailings according to claim 1, characterized in that: The grinding aid is one of sodium stearate and polyolamine, and the amount used is 0.01% to 0.1% of the mass of the machine-made sand tailings.
7. The method for preparing a cement-based material admixture based on machine-made sand tailings according to claim 1, characterized in that: The high-activity lime powder has a calcium oxide content of more than 90 wt % and a particle size of less than 100 μm.
8. The method for preparing a cement-based material admixture based on machine-made sand tailings according to claim 1, characterized in that: The SiO2 content of the nano-silicon dioxide is more than 99wt% and the particle size is less than 100nm.
Citation Information
Patent Citations
Machine-made sand tailing mud self-compacting backfill material based on phosphogypsum and preparation method and application of machine-made sand tailing mud self-compacting backfill material
CN116177974A
Method for preparing high-activity auxiliary cementing material through calcium increasing and thermal activation of sand washing mud
CN118221364A